2015
DOI: 10.1111/1365-2745.12444
|View full text |Cite
|
Sign up to set email alerts
|

Biological Flora of the British Isles:Neottia ovata

Abstract: 1. This account presents information on all aspects of the biology of Neottia ovata (L.) Bluff & Fin-gerh. (Common Twayblade; Listera ovata (L.) R. Br.) that are relevant to an understanding of its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles: distribution, habitat, communities, responses to bio-tic factors, responses to environment, structure and physiology, phenology, reproductive characteristics, herbivores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Most of our studied orchid species harboured a high number of mycorrhizal fungi in their roots, such as Anacamptis morio (similarly reported in Bailarote et al, 2012; Ercole et al, 2015), Gymnadenia conopsea (Těšitelová et al, 2013; Vogt‐Schilb et al, 2020), Neotinea ustulata and Neottia ovata (Djordjević et al, 2016; Kotilínek et al, 2015). Despite the occurrence of multiple fungal associations per species, we demonstrated that only a single or a few fungi were constantly more abundant in orchid roots than the others based on their relative frequencies.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Most of our studied orchid species harboured a high number of mycorrhizal fungi in their roots, such as Anacamptis morio (similarly reported in Bailarote et al, 2012; Ercole et al, 2015), Gymnadenia conopsea (Těšitelová et al, 2013; Vogt‐Schilb et al, 2020), Neotinea ustulata and Neottia ovata (Djordjević et al, 2016; Kotilínek et al, 2015). Despite the occurrence of multiple fungal associations per species, we demonstrated that only a single or a few fungi were constantly more abundant in orchid roots than the others based on their relative frequencies.…”
Section: Discussionsupporting
confidence: 57%
“…Neotinea ustulata and Neottia ovata (Djordjević et al, 2016;Kotilínek et al, 2015). Despite the occurrence of multiple fungal associations per species, we demonstrated that only a single or a few fungi were constantly more abundant in orchid roots than the others based on their relative frequencies.…”
Section: Omf Diversity and Variation Among Orchid Species And Sitesmentioning
confidence: 69%
“…Expected spectra of trophic mode, fungal associations and light availability for Neottia ovata . Compared with the fully mycoheterotrohic N. nidus‐avis (Jersáková et al, 2022) that exclusively associates with ectomycorrhizal fungi (ECM), N. ovata (Kotilínek et al, 2015) is mainly associated with rhizoctonia fungi and hypothesized to be at an early stage of partial mycoheterotrophy (also broadly termed ‘mixotrophy’, Selosse & Roy, 2009). The level of partial mycoheterotrophy is a continuum between autotrophy and full mycoheterotrophy and hypothesized to relate to habitat's light availability.…”
Section: Introductionmentioning
confidence: 99%
“…Common twayblade is one of the widespread orchids in Europe, especially in the British Isles [25]. However, this species is quite seldom encountered in Russia and has the status of a "rare species" in many regional Red Data Books, including the Red Book of Sverdlovsk Region [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, this species is quite seldom encountered in Russia and has the status of a "rare species" in many regional Red Data Books, including the Red Book of Sverdlovsk Region [26]. This is a short-rhizome herbaceous perennial, mesophyte, European-West Asian, boreal-immoral species [3,25,27]. Like other orchids, N. ovata is characterized by low competitiveness.…”
Section: Introductionmentioning
confidence: 99%